Recent therapeutic approaches for spinal cord injury. Issue 2 (2nd September 2015) - Raspa, Andrea; Pugliese, Raffaele; Maleki, Mahboubeh; Gelain, Fabrizio
ABSTRACT: A spinal cord injury (SCI) often causes permanent changes in strength and sensation functions below the site of the injury and affects thousands of people each year. Transplantation of stem cells is a promising approach in acute SCI as it may support spinal cord repair. However, in case of chronic SCI greater amounts of nervous tissue have to be regenerated, leaving scaffold transplantation the only feasible option for cellular engraftment and nervous bridging. The aim of regenerative medicine, specifically tissue engineering, is to create a microenvironment that mimics native extracellular matrix (ECM), capable of promoting specific cell‐matrix interactions, coaxing cell behavior, and fostering host tissue regeneration. In this regard, nanostructured scaffolds are currently the most promising advanced substrates capable of supporting nervous fiber ingrowth and delivery of neurotrophic drugs. Among them, electrospinning technique and Self‐Assembling Peptides (SAPs) have recently attracted lots of attention for their reproducible synthesis and high tailorability. This review highlights clinical trials and recent encouraging strategies for spinal cord repair comprising both cell therapy and nanomedicine. Biotechnol. Bioeng. 2016;113: 253–259. © 2015 Wiley Periodicals, Inc. Abstract : Multidisciplinary (combined) strategies for the treatment of chronic SCI offer bright prospective for future clinical treatments.